THEORETICAL APPROACHES TO THE CONCEPT OF "TAX POTENTIAL" AND METHODS OF ITS ASSESSMENT - Yuldasheva Umida Asanaliyevna (European Science Publishing, 2023)
The study of the theoretical and methodological foundations of the formation of tax levers for the development and regulation of the economy shows that improving the effectiveness of tax policy and the tax system requires the development and implementation of such a strategy of tax reforms, which, guided by the peculiarities of a particular country, is focused on ensuring a balance between the processes of collecting state financial resources and facilitating the activities of economic entities. The tax reforms currently being implemented in the Republic of Uzbekistan are situational in nature and are mainly aimed at ensuring state budget revenues. With this approach, the role of the tax system in regulating economic relations decreases, the volume of shadow turnover increases, economic activity and the desire to carry out economic activity decreases, as well as other negative phenomena appear. The integrity of tax relations in its economic content is a complex system that, when studied, should be divided into interrelated and interdependent subsystems, since their simultaneous and comprehensive consideration, as a rule, becomes practically impossible. Naturally, each country, individual sectors of its economy and relations are endowed with all the features inherent in complex systems that combine various elements with internal and external relations. In this article, in accordance with the draft resolution of the President of the Republic of Uzbekistan “On measures to further improve tax administration and the activities of tax authorities in 2022-2026”, the main activities of tax authorities to create favorable conditions for taxpayers and further improve tax administration are indicated. The article discusses various approaches to the definition of the concept of "tax potential", and also formulated the author's definition. The classification of methods for assessing the tax potential of the region is given. The main advantages and disadvantages of the considered methods are revealed.
Keywords: tax potential, assessment of tax potential, method of representative tax system, method of direct counting, actual method, method of gross regional product, method of per capita income of the population.